Penilaian Kawasan Perumahan dengan Pendekatan Konsep Berkelanjutan (Greenship Neighborhood Assessment) - Sapitri; Zarnold Aziz (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2021)
Global warming and environmental degradation are still being issues in various countries, including Indonesia. It has been causing the climate change. In 2015 the United Nations started a program called Sustainable Development Goals (SDGs). One of the goals was to tackle climate change. In order to encourage the implementation of SDGs, an effort that could conduct was the realization of green housing areas. An assessment is needed to make sure that sustainable development in neighborhood is implemented well and correctly. Green Building Council Indonesia (GBCI) has published a rating system called Greenship Neighborhood as a reference for assessing the concept of sustainable development neighborhood. The purpose of this study was to find out how the implementation of Greenship Neighbourhood and how much value is achieved in Citraland residential area. The methods used were descriptive qualitative and quantitative. Descriptive qualitative was a description of the research object conditions, while descriptive quantitative was output assessments numbers based on the Greenship Neighborhood assessment tool. There were seven aspects that assessed i.e. land ecological enhancement, movement and connectivity, water management and conservation, solid and material waste, community wellbeing strategy, buildings and energy, and innovation future development. The results of research showed that there were six of the seven assessment categories have been applied in the object area. Generally, the total value is 36 out of 124, with percentage achieved 29%. Based on these result, Citraland Pekanbaru residential area did not meet the minimum standard for the application of Greenship Neighborhood according to GBCI.